OP0028 POST-APPROVAL COMPARATIVE SAFETY STUDY OF TOFACITINIB AND BIOLOGIC DMARDS: FIVE–YEAR RESULTS FROM A US-BASED RHEUMATOID ARTHRITIS REGISTRY. (June 2019) - Kremer, Joel; Bingham, Clifton; Cappelli, Laura; Etzel, Carol; Greenberg, Jeffrey; Geier, Jamie; Madsen, Ann; Chen, Connie; Onofrei, Alina; Barr, Christine; Pappas, Dimitrios A.; Litman, Heather J.; et al.
Abstract : Background: Tofacitinib is an oral JAK inhibitor for the treatment of rheumatoid arthritis (RA). Real-world data (RWD) complement clinical trial data in assessing long-term safety. To our knowledge, this is the first long-term comparative RWD analysis of tofacitinib. Objectives: To compare 5-year adverse event (AE) incidence rates (IRs) in patients (pts) starting tofacitinib vs biological (b)DMARDs using cohorts from the US Corrona RA registry. Methods: This prospective, observational 5-year study embedded in the ongoing US Corrona RA registry routinely collected 9 categories of predefined AEs from participating physicians. Real-world safety event rates of major adverse cardiovascular events (MACE), serious infectious events (SIEs) and herpes zoster (HZ; serious and non-serious) were compared in pts with RA who started tofacitinib or a bDMARD regardless of dose/schedule between 6 Nov 2012 (US FDA approval) and 30 Jun 2017 (follow-up through 31 Dec 2017). Endpoints were selected a priori as having sufficient power to detect a 2-fold difference between cohorts at this datacut; there was insufficient power to assess malignancy. Baseline variables with a standardised difference >│0.10│ between tofacitinib and bDMARD initiators, and a priori selected covariates (gender, age, line of therapy, history of AE of interest) were used to construct propensity scores (PS) to derive a PS-trimmed (primary) population and a PS–matched population for sensitivity analysis (ratio: max. 4 bDMARD:1 tofacitinib; calliper=0.05). Pts were followed from initiation until an AE of interest, discontinuation and/or start of a new therapy +90 days, death or end of follow-up, whichever came first. Crude IRs (events/100 pt–years [PY]) were estimated; multivariable-adjusted Cox regression was used to estimate hazard ratios (HRs) comparing rates of first events between cohorts. Results: In total, 1544 tofacitinib (2138.2 PY) and 7083 bDMARD (9904.9 PY) initiators were included. PS–trimming resulted in 1117 tofacitinib and 5542 bDMARD initiators. Rates of MACE and SIEs were similar in both cohorts (Fig 1A); adjusted HRs (95% confidence intervals [CIs]) were: MACE 0.60 (0.30, 1.18); SIEs 0.99 (0.72, 1.36; Fig 1B). HZ IR was higher for tofacitinib vs bDMARDs (Fig 1A); HRs for HZ were significantly increased with tofacitinib vs bDMARDs (adjusted HR 2.12 [1.22, 3.66]; Fig 1B); all HZ events were non-serious with tofacitinib. Similar results were observed in PS-matched populations. Conclusion: This is the first comparative analysis of RWD for tofacitinib and bDMARDs to use PS-trimmed and PS-matched analyses to adjust for channelling/prescribing patterns for newly approved therapies. Pts starting tofacitinib or bDMARDs for RA had similar rates of MACE and SIEs. Tofacitinib initiators had higher HZ IRs vs bDMARD initiators. These results are consistent with long-term clinical trial findings. Acknowledgement: Sponsors: Corrona, LLC. Corrona is supported by contracted subscriptions with multiple companies. This was a Corrona/Pfizer collaboration with Pfizer financial support. Medical writing support provided by Anthony G McCluskey of CMC Connect and funded by Pfizer Inc. Disclosure of Interests: Joel Kremer Grant/research support from: AbbVie, Genentech, Lilly, Novartis, Pfizer, Consultant for: AbbVie, Amgen, BMS, Genentech, Lilly, Regeneron, Sanofi, Pfizer, Clifton Bingham Grant/research support from: BMS, Consultant for: AbbVie, BMS, Eli Lilly, Genentech/Roche, Janssen, Pfizer, Sanofi/Regeneron, Laura Cappelli Grant/research support from: Bristol-Myers Squibb, Consultant for: Regeneron/Sanofi Genzyme, Carol Etzel Shareholder of: Corrona, LLC, Consultant for: Merck, Employee of: Corrona, LLC, Jeffrey Greenberg Shareholder of: Corrona, LLC, Consultant for: Eli Lilly, Genentech, Janssen, Novartis, and Pfizer Inc, Employee of: Corrona, LLC, Jamie Geier Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Ann Madsen Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Connie Chen Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Alina Onofrei Employee of: Corrona, LLC, Christine Barr Shareholder of: Corrona, LLC, Employee of: Corrona, LLC, Dimitrios A Pappas Grant/research support from: AbbVie, Consultant for: AbbVie, Employee of: Corrona, Heather J. Litman: None declared, Kimberly J Dandreo Employee of: Corrona, LLC, Andrea Shapiro Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Carol A. Connell Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Arthur Kavanaugh Grant/research support from: UCB Pharma